TRPV4 Mediates Acute Bladder Responses to Bacterial Lipopolysaccharides - Alpizar, Yeranddy A.; Uvin, Pieter; Naert, Robbe; Franken, Jan; Pinto, Silvia; Sanchez, Alicia; Gevaert, Thomas; Everaerts, Wouter; Voets, Thomas; De Ridder, Dirk; Talavera, Karel (Frontiers in Immunology, 2020)
Urinary tract infections (UTI) affect a large proportion of the population, causing among other symptoms, more frequent and urgent micturition. Previous studies reported that the gram-negative bacterial wall component lipopolysaccharides (LPS) trigger acute epithelial and bladder voiding responses, but the underlying mechanisms remain unknown. The cation channel TRPV4 is implicated in the regulation of the bladder voiding. Since TRPV4 is activated by LPS in airway epithelial cells, we sought to determine whether this channel plays a role in LPS-induced responses in urothelial cells (UCs). We found that human-derived UCs display a fast increase in intracellular Ca2+ concentration upon acute application of E. coli LPS. Such responses were detected also in freshly-isolated mouse UCs, and found to be dependent on TRPV4, but not to require the canonical TLR4 signaling pathway of LPS detection. Confocal microscopy experiments revealed that TRPV4 is dispensable for LPS-induced nuclear translocation of NF-B in mouse UCs. On the other hand, quantitative RT PCR determinations showed an enhanced LPS-induced production of proinflammatory cytokines in TRPV4-deficient UCs. Cystometry experiments in anesthetized wild type mice revealed that acute intravesical instillation of LPS rapidly increases voiding frequency. This effect was not observed in TRPV4-deficient animals, but was largely preserved in Tlr4 KO and Trpa1 KO mice. Our results suggest that activation of TRPV4 by LPS in UCs regulates the proinflammatory response and contributes to LPS-induced increase in voiding frequency. These findings further support the concept that TRP channels are sensors of LPS, mediating fast innate immunity mechanisms against gram-negative bacteria.